Identification, Expression and Activity of Candidate Nitrite Reductases From Orange Beggiatoaceae, Guaymas Basin - Buckley, Andrew; MacGregor, Barbara; Teske, Andreas (Frontiers in Microbiology, 2019)
Orange filamentous Beggiatoaceae form massive microbial mats on hydrothermal sediments in Guaymas Basin; these bacteria are considered to oxidize sulfide with nitrate and nitrite as electron acceptors. From a previously analyzed genome of an orange Beggiatoaceae filament, three candidate genes for enzymes with nitrite-reducing function – an orange octaheme cytochrome, a nirS nitrite reductase, and a nitrite/tetrathionate-reducing octaheme cytochrome - were cloned and expressed in E.coli. The expressed and purified orange cytochrome showed reduced nitrite-reducing activity compared to the multifunctional native protein obtained from microbial mats. The nirS gene product showed in vitro but no in-gel nitrite-reducing activity; and the nitrite/tetrathionate-reducing octaheme cytochrome was capable of reducing both nitrite and tetrathionate in vitro. Phylogenetic analysis shows that the orange Beggiatoaceae nirS, in contrast to the other candidate nitrite reductases, does not form monophyletic lineages with its counterparts in other large sulfur-oxidizing bacteria, and most likely represents a recent acquisition by lateral gene transfer. The nitrite/tetrathionate-reducing enzyme of the orange Beggiatoaceae is related to nitrite- and tetrathionate reductases harbored predominantly by Gammaproteobacteria, including obligate endosymbionts of hydrothermal vent tubeworms. Thus, the orange Guaymas Basin Beggiatoaceae have a repertoire of at least three different functional enzymes for nitrite reduction. By demonstrating the unusual diversity of enzymes with a potential role in nitrite reduction, we show that bacteria in highly dynamic, sulfide-rich hydrothermal vent habitats adapt to these conditions that usually prohibit nitrate and nitrite reduction. In the case of the orange Guaymas Beggiatoaceae, classical denitrification appears to be replaced by different multifunctional enzymes for nitrite and tetrathionate reduction; the resulting ecophysiological flexibility provides a new key to the dominance of these Beggiatoaceae in hydrothermal hot spots.